Balance response time in a multiserver information system environment - LEE, Francis Bu Sung (Institutional Knowledge at Singapore Management University, 1997)
As information systems move from centralized to distributed systems, the distribution of the data files among the servers becomes a major issue. This paper reports on the results of a heuristic algorithm that is used to distribute the files among multiple heterogeneous servers interconnected by a fast network. The objective of our algorithm is to minimize the differences between response times of the servers (or in other words, to minimize the response imbalance factor). The servers are modeled using M/M/1 queues. In this paper, we first describe the problem, then the algorithm is presented and its bounds on the imbalance factor analyzed. The characteristics of our algorithm are also studied through simulation. Results are compared with the algorithms proposed by other researchers, which show a considerable improvement in the imbalance factor and only a slight increase in the average response time of the system.